Daily Behavior of Reintroduction Candidate Orangutans (Pongo pygmaeus) at Jerora Forest School, Sintang Orangutan Center, West Kalimantan - Nauhal Nazri Halim; Luthfiralda Sjahfirdi; Tatang Mitra Setia (Jurnal Penelitian Pendidikan IPA, 2025)
Bornean orangutans (Pongo pygmaeus) in captivity require time to be released in order to survive in their natural habitat. This study aims to analyze the daily behavior of orangutans awaiting release at the Jerora Forest School, Sintang Orangutan Center, West Kalimantan. The study was conducted using a focused animal observation method with 5-minute intervals without breaks and without time restrictions. Observations were made on two female orangutans, Jamilah (24 years old) and Penai (21 years old). The results of the data analysis showed that Jamilah's feeding behavior occurred in the enclosure (41.89%) and cage (38.49%), while Penai's feeding behavior occurred in the enclosure (31.41%) and cage (41.22%). The least frequent behavior was playing, with Jamilah playing in the enclosure (4.87%) and cage (3.95%) and Penai playing in the enclosure (4.02%) and cage (3.84%). Jamilah's arboreal movement behavior was 62% and Penai's was 82%. The observation results indicate that Jamilah is more ready for release than Penai based on the orangutan release readiness criteria cited from the Orangutan Conservation and Reintroduction Workshop in 2002.